PENGARUH KOMITMEN KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA ASN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING PADA DINAS PETERNAKAN DAN PERIKANAN KABUPATEN SITUBONDO - Agustin, Rika Dwi; Arief, Mohammad Yahya; Wiryaningtyas, Dwi Perwitasari (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of the study was to determine the effect of service and price on purchasing decisions through product quality at Waroeng Kopi Kayu Mas, Asembagus District, Situbondo. The sampling technique used in this study was simple random sampling with the Slovin formula with a tolerable error rate of 10% as many as 95 people. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that service has a positive and significant effect on product quality, price has a positive and significant effect on product quality. Service has a positive and significant effect on purchasing decisions. Price has a positive and significant effect on purchasing decisions. Product quality has a positive and significant effect on purchasing decisions, service has a positive and insignificant effect on purchasing decisions through product quality, price has a positive and significant effect on purchasing decisions through product quality